2021
DOI: 10.3389/fpsyg.2021.613055
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Education in COVID Lockdown: More Anxious and Less Creative—Maybe Not?

Abstract: Secondary education around the world has been significantly disrupted by covid-19. Students have been forced into new ways of independent learning, often using remote technologies, but without the social nuances and direct teacher interactions of a normal classroom environment. Using data from the School Attitudes Survey—which surveys students regarding the perceived level of difficulty, anxiety level, self-efficacy, enjoyability, subject relevance, and opportunities for creativity with regards to each of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
(27 reference statements)
0
5
0
2
Order By: Relevance
“…Hence, SCC relies on a self-rating of one’s own creativity. Similar self-report scales or ratings measuring creativity belief, self-concept, and self-efficacy have been developed ( Beghetto, 2006 ; Ng and Feldman, 2012 ; Karwowski and Barbot, 2016 ; Karwowski and Lebuda, 2016 , 2017 ; Karwowski et al, 2019 ) and used in COVID-19-related studies ( Hofreiter et al, 2021 ; Mercier et al, 2021 ; Patston et al, 2021 ). In contrast to these previous measures, we asked participants to rate a change in their creativity related to a key event (i.e., the beginning of the lockdown).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, SCC relies on a self-rating of one’s own creativity. Similar self-report scales or ratings measuring creativity belief, self-concept, and self-efficacy have been developed ( Beghetto, 2006 ; Ng and Feldman, 2012 ; Karwowski and Barbot, 2016 ; Karwowski and Lebuda, 2016 , 2017 ; Karwowski et al, 2019 ) and used in COVID-19-related studies ( Hofreiter et al, 2021 ; Mercier et al, 2021 ; Patston et al, 2021 ). In contrast to these previous measures, we asked participants to rate a change in their creativity related to a key event (i.e., the beginning of the lockdown).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, education outside of the school environment offered the opportunity for independence to be developed in students, allowing self-reflection and focus outside of peer influence and pressure [152]. The unconventional educational methods enabled innovation and creativity in both educators and students [153], possibly due to the exploration of new learning methodologies in a different educational context [154]. Creativity is considered a vital ability in students [155] and has played a key role in managing the pandemic-related difficulties [156].…”
Section: Skill Developmentmentioning
confidence: 99%
“…Creativity is considered a vital ability in students [155] and has played a key role in managing the pandemic-related difficulties [156]. Lastly, research has shown that the greater the creativity demonstrated by students, the less anxiety they experienced [154].…”
Section: Skill Developmentmentioning
confidence: 99%
“…The stories of suffering during the pandemic will no doubt continue to emerge, but there is also a strand of scholarship that shows how humans have responded to adversity with tenacity. For example, some students thrived academically during remote learning (Hammerstein et al, 2021), and others have shown emotional resilience during school closures (Patston et al, 2021;Luthar et al, 2021). Narratives that foreground teacher voices have shown educators taking pride in "finding a way" for their students (Kim and Asbury, 2020).…”
mentioning
confidence: 99%